OPTIONAL CHARACTERISTICS RELATED TO THE CITIZENSHIP OF THE OFFENDER - Karaketova Dilnoza Yuldashevna (Modern American Journals, 2025)
The article explores, from both theoretical and practical perspectives, the characteristics associated with an offender’s citizenship. The author notes that the expansion of international migration, tourism, and labor mobility has led to an increase in crimes committed with the participation of foreign nationals and stateless persons. An analysis of judicial practice reveals that, in certain cases, courts in our country have imposed sentences guided by the principles of liberalism and humanism. At the same time, when determining punishment for foreign citizens, special significance is attached to the norms of international law, as well as to the principles of extraterritoriality and immunity. Having identified the existing challenges, the author emphasizes the need to address legislative gaps concerning the criminal liability of foreign nationals and stateless persons, and puts forward proposals aimed at improving a number of provisions of the Criminal Code.
Keywords: Subject of crime, citizenship, foreign national, stateless person, international law, criminal liability, immunity, extraterritoriality, judicial practice, liberal approach.